Outcomes of COVID-19 in the Omicron-predominant wave: large-scale real-world data analysis with a comparison to influenza - Koichi Miyashita; Hironao Hozumi; Kazuki Furuhashi; Eiji Nakatani; Yusuke Inoue; Hideki Yasui; Yuzo Suzuki; Masato Karayama; Noriyuki Enomoto; Tomoyuki Fujisawa; Naoki Inui; Toshiyuki Ojima; et al. (Pneumonia)
Abstract Purpose Studies on COVID-19 mortality during the Omicron-predominant wave have focused primarily on the inpatient/emergency room setting, and real-world data including both inpatients and outpatients are lacking. Methods Patients diagnosed with COVID-19 (n = 27,440,148) or influenza (n = 8,179,641) from January 2020 to April 2023 were identified using nationwide claims data in Japan. Patients with COVID-19 in the Omicron-predominant wave were compared with their counterparts in earlier waves, and a subset of the former group (May 2022–April 2023) was compared with patients with influenza as controls. Results The mortality rates (average number of deaths/cases per week) of COVID-19 decreased over time, being 2.7% (169/6312), 2.1% (397/18,754), 0.7% (195/28,273), and 0.4% (1613/378,848) in the wild-type–, Alpha-, Delta-, and Omicron-predominant waves, respectively. However, the number of deaths increased substantially in the Omicron-predominant wave, especially among the elderly (e.g., in the Delta- and Omicron-predominant waves, the average numbers of deaths/cases per week were < 1/5527 (< 0.01%) and 4/105,763 (< 0.01%) respectively, in patients aged 0–19, versus 101/925 (10.9%) and 1212/20,771 (5.8%), respectively, in patients aged ≥ 80). The mortality rate was lower for patients with COVID-19 than in those with influenza among those aged ≤ 39 years but higher among those aged ≥ 40 years. Conclusions In the Omicron-predominant wave, the mortality rate of COVID-19 decreased, but the number of patients increased, leading to a substantial increase in the number of deaths, especially among the elderly. The mortality rate of COVID-19 was higher than that of influenza in the elderly but not in the young, highlighting the need for age-specific interventions.